2021
DOI: 10.51920/jd.v11i1.183
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Akuntansi Pencatatan Penerimaan Kas Pada Pt. Mega Vision Mandiri

Abstract: ABSTRAK PT. Mega Vision Mandiri adalah perusahaan yang bergerak dibidang telekomunikasi dan komunikasi yang memberikan layanan kepada masyarakat dengan memberikan tayangan televisi dengan audio visual berkualitas jernih. Dengan memberikan tayangan-tayangan yang bermutu dan mendidik, Seperti channel be In Sport 1, Fox Family Movies, Discovery Channels dan Makkah Live. Tayangan televisi yang diberikan oleh perusahaan kepada pelanggan sangat diharapakan bisa dapat mendidik dan juga mencerdaskan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…After the program encoding is done, the built system will be tested to see if it is in line with the plan or not. And at the final stage of the maintenance process, which is the development, repair, and maintenance phase of the system that has been built (Amrullah et al, 2021).…”
Section: System Development Methodsmentioning
confidence: 99%
“…After the program encoding is done, the built system will be tested to see if it is in line with the plan or not. And at the final stage of the maintenance process, which is the development, repair, and maintenance phase of the system that has been built (Amrullah et al, 2021).…”
Section: System Development Methodsmentioning
confidence: 99%
“…In this case, cash receipts will be deposited with the central company because the funds received are temporary. In previous research, this cash receipt and expenditure application was found to be very useful, as it can help carry out cash recordings (Alista et al, 2021;Amrullah et al, 2021) as well as facilitate work in data management (Ari Indraswati, 2021;Kristeria et al, 2020). Even information systems can help companies with decision-making (Hayat et al, 2019;Misran, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Maintenance, is the stage of development, improvement, and maintenance of a system that has been built (Amrullah et al, 2021).…”
mentioning
confidence: 99%